Mechanical and chemical resistance of composite materials with addition of anaerobic digestate. (1st May 2016) - Taurino, Rosa; Lancellotti, Isabella; Tatàno, Fabio; Carchesio, Manuela; Pozzi, Paolo
Abstract: Bioenergy, produced through the anaerobic digestion (AD) of renewable organic feedstocks, is considered to be one of the highly promising alternatives to fossil-derived energy. The anaerobic digestion residues have recently begun to be recognized as underutilized natural resources that have unrecognized value. This work is focused on the new added valorization of digestates obtained from the AD of organic substrates. Effect of digestates treatments and concentration on the properties of composites were investigated. The results showed an increase of mechanical and chemical resistance of the composites as a result of the heat treatment of digestates. Composite having 30% unsilanized calcined-digestate fillers was found to have the highest chemical and mechanical properties.